Piper betle L. Silver Nanoparticle-Synthesis, Characterization and Antibacterial Study - Karunakaran, Leela; Singh, Anita Rosemarie Joseph (Asian Journal of Biological and Life Sciences, 2025)
Background: Development of nano-based drugs has gained huge attention globally and is widely preferred in healthcare industry specifically due to its smaller size and high loading efficiency for targeted drug delivery. Apart from health care, the application of nanoparticle has expanded in various sectors for different purposes. The synthesis of nanoparticle from natural sources is in huge demand since the process is convenient, no harsh chemicals are used, highly efficient and utilizes natural bioactive compounds as reducing agents. Aim: The present study aims to characterize silver nanoparticle synthesized using aqueous extracts from Piper betle L. leaves and determining their antibacterial potential. Materials and Methods: Silver nanoparticle synthesis was carried out employing aqueous extracts from Piper betle L. leaves with 1 mM concentration of silver nitrate and characterized by means of UV-visible analysis, Particle size analysis, FTIR analysis, SEM with EDAX analysis and Zeta potential analysis. It was determined for its antibacterial activity against Streptococcus mutans, Staphylococcus aureus, Klebsiella pneumoniae, Enterobacter spp. and Salmonella typhi. Results: Silver nanoparticle was synthesized and confirmed by the formation of dark brown colour. Characterization studies revealed peak formation at the wavelength of 392.6 nm, presence of functional groups, spherical shaped and monodispersed silver nanoparticle with polydispersity index of 0.288 and 70.60% silver content confirming the stability of nanoparticle and its ability in inhibiting the bacterial pathogens. Conclusion: This study highlights silver nanoparticle biosynthesis using aqueous extracts from Piper betle L. leaves as well as its antibacterial activity against different pathogenic organisms.
Keywords: Antibacterial activity; Characterization; Piper betle L.; Silver nanoparticle